2018
DOI: 10.1128/jcm.01932-17
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Increase in Prevalence of Carbapenem-Resistant Enterobacteriaceae (CRE) and Emergence of Colistin Resistance Gene mcr-1 in CRE in a Hospital in Henan, China

Abstract: The global spread of carbapenem-resistant (CRE) is one of the most severe threats to human health in a clinical setting. The recent emergence of plasmid-mediated colistin resistance gene among CRE strains greatly compromises the use of colistin as a last resort for the treatment of infections caused by CRE. This study aimed to understand the current epidemiological trends and characteristics of CRE from a large hospital in Henan, the most populous province in China. From 2014 to 2016, a total of 7,249 isolates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 21 publications
4
48
2
3
Order By: Relevance
“…The emergence of carbapenem-resistant Enterobacteriaceae (CRE) strains is a major burden for public health-care systems, 39,40 with long-term surveillance studies identifying emerging high-risk strains of CRKP. 41,42 Here, we analyzed a 14-year time-window for trends in resistance phenotypes, virulence factors and sequence profiles of CRKP isolates from a major hospital in Wenzhou.…”
Section: Discussionmentioning
confidence: 99%
“…The emergence of carbapenem-resistant Enterobacteriaceae (CRE) strains is a major burden for public health-care systems, 39,40 with long-term surveillance studies identifying emerging high-risk strains of CRKP. 41,42 Here, we analyzed a 14-year time-window for trends in resistance phenotypes, virulence factors and sequence profiles of CRKP isolates from a major hospital in Wenzhou.…”
Section: Discussionmentioning
confidence: 99%
“…In Asia, the prevalence of CRE among clinical samples was determined in many studies includes Rao A et al 17 (India), Amjad A et al 18 (Pakistan), Jamal WY et al 19 (Kuwait), Li Y et al 20 (China), Kandeel A et al 21 (Saudi Arabia), Nair PK et al 22 (India), Zaidah A et al 23 (Malaysia), Jan R et al 24 (South India) and Khare V et al 25 (India) which reported the prevalence of CRE were 13.95%, 69%, 8%, 18.1%, 1.77% ,12.26%, 5.76%, 8% and 37.9% respectively. 17−25 Europe, Australia, and America (North and South)…”
Section: Asiamentioning
confidence: 99%
“…Carbapenems and tigacycline were rarely used in E. coli group when admitted to hospital, thus, the resistance rate was significantly lower in this group. However, with drug-resistant genes resulting in drug-resistant bacteria, they can widely spread in hospitals and communities, consequently resulting in an increased incidence of carbapenem-resistant E. coli and CR K. pneumoniae infections in China [42]. In China, ST11 has been considered as the dominant CR K. pneumoniae strain, but new ST11 CR A. baumannii is emerging [43], which is hypervirulent, multidrug resistant, and transmissible, potentially resulting a real superbacteria that could pose a serious threat to public health.…”
Section: Drug Resistancementioning
confidence: 99%
“…In China, ST11 has been considered as the dominant CR K. pneumoniae strain, but new ST11 CR A. baumannii is emerging [43], which is hypervirulent, multidrug resistant, and transmissible, potentially resulting a real superbacteria that could pose a serious threat to public health. The polycolisin-resistant E. coli has been found in China [42], which undoubtedly adds to the current sad situation.…”
Section: Drug Resistancementioning
confidence: 99%